Cassava breeding at IITA: Conference Proceedings of the Third Symposium of the International Society for Tropical Root Crops held at IITA, Ibadan, Nigeria, 29 December, 1973 - Hahn, S.K.; Howland, A.K.; Terry, Eugene R. (1977)
The breeding objectives in the Root and Tuber Improvement Programme of the International Institute of Tropical Agriculture (IITA) were laid down. Basic considerations in cassava breeding were reviewed and discussed. The paper attempts to produce a cassava breeding system applicable on a world-wide basis and describes the present state and the future development of cassava breeding.